2020
DOI: 10.3390/foods9020195
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Vitamin D-Specific Food Frequency Questionnaire against Food Records for Qatari Women

Abstract: The measurement of vitamin D nutritional status through dietary assessment is cost effective. Food frequency questionnaire (FFQ) is usually validated against food records (FR). There is no vitamin D-specific FFQ for Qatar population. The objective of this study was to develop a vitamin D-centric FFQ and validate FFQ against three-day FR for Qatar population. A quantitative FFQ based on vitamin D containing foods consumed in Qatar was developed. Vitamin D contents of foods were gathered from food labels and foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…Although there have been previous vitamin D FFQ validation studies (18,(20)(21)(22) , these have been carried out in countries including Northern Ireland, the USA, Canada and Qatar. The dietary habits of those populations are likely to differ from those of English participants.…”
mentioning
confidence: 99%
“…Although there have been previous vitamin D FFQ validation studies (18,(20)(21)(22) , these have been carried out in countries including Northern Ireland, the USA, Canada and Qatar. The dietary habits of those populations are likely to differ from those of English participants.…”
mentioning
confidence: 99%
“…Measurement of food intakes using 24HFR requires trained interviewers to gather data from the subjects. Earlier, we have validated an FFQ with three-day food records and found an agreement between vitamin D intakes from FFQ and three-day food records (Ganji et al, 2020). Djekic-Ivankovic et al (2016) reported that FFQ was a valid tool for the assessment of vitamin D intakes in young Serbian women.…”
Section: Vitamin D Food Intake Assessment 4823mentioning
confidence: 88%
“…The BA plot is widely used for assessing the agreement between two assessment tools (Głąbska et al. , 2016; Ganji et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The present study has some limitations. First, measurement errors are inevitable because dietary intakes was determined using FFQ which might have led to over- or under- estimation of habitual intake as a recall bias (Ganji et al , 2020; Steinemann et al , 2017); however, we used a FFQ, which its reliability and validity have been reported previously (Mirmiran et al , 2010); moreover, individuals were excluded if they had under-/over-reporting on energy intakes. Second, individuals in control group had hepatic related diseases, which could be effective on the association of dietary intakes and NAFLD due to sharing the exposure; however, we preferred clinical controls (as opposed to community controls) due to their higher participation and cooperation rates and to avoid selection bias (Lewallen and Courtright, 1998).…”
Section: Discussionmentioning
confidence: 99%